The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00018-017-2634-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of CRMP5 controls neurite outgrowth through Sox5

Abstract: Transcriptional regulation of proteins involved in neuronal polarity is a key process that underlies the ability of neurons to transfer information in the central nervous system. The Collapsin Response Mediator Protein (CRMP) family is best known for its role in neurite outgrowth regulation conducting to neuronal polarity and axonal guidance, including CRMP5 that drives dendrite differentiation. Although CRMP5 is able to control dendritic development, the regulation of its expression remains poorly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Some lncRNAs could combine with microRNAs and form complex regulatory networks, and then modulate the expression and function of microRNAs 30 , 31 . In addition, noncoding RNAs ordinarily form ribonucleoprotein (RNP) complexes with their partner proteins to exert their functions and miRNAs assemble with argonaute (Ago) family proteins into the effector complex called RISC that mediates the target gene silencing 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Some lncRNAs could combine with microRNAs and form complex regulatory networks, and then modulate the expression and function of microRNAs 30 , 31 . In addition, noncoding RNAs ordinarily form ribonucleoprotein (RNP) complexes with their partner proteins to exert their functions and miRNAs assemble with argonaute (Ago) family proteins into the effector complex called RISC that mediates the target gene silencing 32 .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the role of GATA4 and GATA5 in heart development and angiogenesis and the role of GATA4 in neuronal development and function (Lawson and Mellon 1998;Holtzinger and Evans 2007;Walsh and Shiojima 2007;Ang et al 2016). Similarly, genes that contain more than one copy of the UW.Motif.0167 in their promoters are associated with dendritic spine development, among other biological processes, as are SOX2, SOX5, and SOX11 (Whitney et al 2014;Hoshiba et al 2016;Naudet et al 2018). Altogether, this shows that our approach can identify TFs that bind to uncharacterized motifs, including zinc fingers, which are generally difficult to study, and that the TFs identified are likely to be functionally related to their potential target genes.…”
Section: Ey1h Assays For Variants and Repetitive Elementssupporting
confidence: 79%
“…This is consistent with the role of GATA4 and GATA5 in heart development and angiogenesis, and the role of GATA4 in neuronal development and function (Lawson and Mellon 1998;Holtzinger and Evans 2007;Walsh and Shiojima 2007;Ang et al 2016). Similarly, genes that contain more than one copy of the UW.Motif.0167 in their promoters are associated with dendritic spine development, among other biological processes, as are SOX2, SOX5, and SOX11 (Whitney et al 2014;Hoshiba et al 2016;Naudet et al 2018). Altogether, this shows that our approach can identify TFs that bind to uncharacterized motifs, including zinc fingers which are generally difficult to study, and that the TFs identified are functionally related to their potential target genes.…”
Section: Novel Dna Motifssupporting
confidence: 79%